Sintering and characterisation of nano-sized yttria-stabilised zirconia. (24th March 2008) - Hasanuzzaman, M.; Rafferty, A.; Olabi, A.G.; Prescott, T.
Two types of commercially available nano-sized, ZrO2?3mol%Y2O3 (Y-Tetragonal Zirconia Polycrystals (TZP)) powders were investigated. BET surface area analysis showed the powders to be nano-sized as determined using Equivalent Spherical Diameter (ESDBET) theory. Dilatometry analysis showed that one of the powders underwent complete shrinkage during isothermal sintering; the other did not. The point of maximum densification rate for the powders differed by approximately 100?C. A dramatic expansion associated with the tetragonal to monoclinic transformation was observed by dilatometry for unstabilised zirconia, but not for TZP samples. X-ray diffraction showed that the starting TZP powders contained some monoclinic zirconia, but confirmed that discs sintered from this powder were wholly tetragonal. For one powder type, the fracture toughness of discs decreased almost linearly with increasing sintering temperature, whereas for the other the fracture toughness was relatively stable across the temperature range. Two-step sintering enabled a maximum fracture toughness of 6.12 MPa m1/2 to be achieved.